5-Aminouracil as Effective Inhibitor of Peroxyl Radicals. Experimental and Theoretical Studies - A. Grabovskiy, Stanislav; G. Konkina, Irina; I. Murinov, Yuri; N. Kabal'nova, Natalia (Current Organic Chemistry, 2012)
The reaction of 5-aminouracil with peroxyl radicals generated by the thermal decomposition of 2,2'-azo-bis(2- methylpropionitrile) (AIBN) and 2,2'-azo-bis(2-amidinopropane) dihydrochloride was studied at 50°C in ethanol and water (pH 7.0) solution respectively. The oxidation product of 5-aminouracil formed by peroxyl radicals was dihydro-5,5,6-trihydroxypyrimidine-2,4-dione. The relative rate constant of 5-aminouracil vs. quercetin and 2,6-di-tert-butyl-4-methylphenol by peroxyl radicals generated from AIBN was measured in ethanol and found to be 0.19 (50°C) and 3.6 (70°C) respectively. Theoretical data of the redox potential and the bound dissociation energy oppose against single electron/proton transfer mechanism and provide support for a hydrogen atom abstraction mechanism. Transition structures and activation barriers of the hydrogen abstraction from 5-aminouracil, 5-hydroxy-6-methyluracil and 2,6-di-tert-butyl-4-methylphenol by methyl peroxyl radical were determined with the BB1K/6-31+G(d,p) level of theory. The relative theoretical reactivity was found to be in a good agreement with the experimental results and also supported the hydrogen abstraction mechanism.
Keywords: Relative rate constant